Small Grain Variety Trials - Stefan Gailans; Emma Link; Kenneth Pecinovsky (Hello World!, 2024)
Careful management and proper variety selection can make small grains profitable in crop rotations due to their low input requirements and beneficial effects on succeeding crops. When grown as a cash crop cereal rye and oats can be marketed for cover crop seed, grain, straw, forage, hay or haylage. Their mid-summer harvest allows for a myriad of field management options for the remainder of the season, such as mid-season manure application or the establishment of a perennial forage crop.